2018
DOI: 10.1021/acschemneuro.8b00226
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Nascent APP in Hippocampal Neurons: A Live Cell Imaging Study

Abstract: Amyloid precursor protein (APP) is closely associated with Alzheimer's disease (AD) because its proteolytic products form amyloid plaques and its mutations are linked to familial AD patients. As a membrane protein, APP is involved in neuronal development and plasticity. However, it remains unclear how nascent APP is distributed and transported to designated membrane compartments to execute its diverse functions. Here, we employed a dual-tagged APP fusion protein in combination with a synaptic vesicle marker to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…APP modifications and trafficking are mutually regulated, contributing in turn to the modulation of Aβ generation [45]. The acquisition of APP post-translational modifications occurs mainly during the passage through the secretory pathway in neurons [42,46], where the protein can undergo glycosylation which starts in the ER to proceed through the Golgi, where sulfation and phosphorylation occur. Since we found that a reduced level of mature APP in AD-affected cells was accompanied by a mislocalization of the APP from the Golgi and consequent accumulation into recycling endosomes (Figure 3, Figures S1 and S2), we speculated that the APP was not able to be correctly modified for maturation probably because of its inability to transit through the secretory pathway and to reach the Golgi apparatus, where the majority of the APP modifications occurs.…”
Section: Discussionmentioning
confidence: 99%
“…APP modifications and trafficking are mutually regulated, contributing in turn to the modulation of Aβ generation [45]. The acquisition of APP post-translational modifications occurs mainly during the passage through the secretory pathway in neurons [42,46], where the protein can undergo glycosylation which starts in the ER to proceed through the Golgi, where sulfation and phosphorylation occur. Since we found that a reduced level of mature APP in AD-affected cells was accompanied by a mislocalization of the APP from the Golgi and consequent accumulation into recycling endosomes (Figure 3, Figures S1 and S2), we speculated that the APP was not able to be correctly modified for maturation probably because of its inability to transit through the secretory pathway and to reach the Golgi apparatus, where the majority of the APP modifications occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in the normal situation (Fig. 3), after a threshold is exceeded, the excess of cholesterol in the plasma membrane [161] binds to full-length A␤PP [162,163] and induces its internalization by the formation of cholesterol-rich endosomes. Following cleavage of A␤PP by BACE1 within endolysosomes to produce C99, C99 traffics to the ER where it "attracts" cholesterol (at 1:1 stoichiometry [117]) [116,117] and sphingomyelin [149], resulting in the formation of a lipid raft domain.…”
Section: What Is the Function Of C99?mentioning
confidence: 99%
“…158 The approach is also applicable to the study of processing of amyloid precursor protein (APP) fused with two fluorescent proteins at its two terminis. [159][160][161] After b-secretase-mediated cleavage, differential subcellular sorting of the N-and C-terminal APP fragments could be tracked within the cell. 159,160 Many proteolytic proteoforms are small peptides, which are impossible to tag with large fluorescent proteins 164 nor specifically detected with antibodies.…”
Section: Detection Of Proteolytic Proteoformsmentioning
confidence: 99%